2013
DOI: 10.1186/1471-2180-13-205
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of a mycorrhization helper bacterium and a mycorrhizal fungus in plant-soil microcosms at different levels of complexity

Abstract: BackgroundHost plant roots, mycorrhizal mycelium and microbes are important and potentially interacting factors shaping the performance of mycorrhization helper bacteria (MHB). We investigated the impact of a soil microbial community on the interaction between the extraradical mycelium of the ectomycorrhizal fungus Piloderma croceum and the MHB Streptomyces sp. AcH 505 in both the presence and the absence of pedunculate oak microcuttings.ResultsSpecific primers were designed to target the internal transcribed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…Previous studies have demonstrated that Streptomyces sp. AcH 505 can promote the mycorrhizal colonization rate at different stages of bacteriumefunguseplant interactions, including spore germination, thereby acting as a mycorrhizal helper bacteria (Riedlinger et al, 2006;Tarkka and Frey-Klett, 2008;Kurth et al, 2013). In the present study Streptomyces fostered the growth of P. croceum in oaks at stage B, according to the higher amounts of specific FA biomarkers for the respective symbiont (18:1 u9 and 18:2 u6,9) at second harvest.…”
Section: Effect Of Pratylenchus Penetrans and Streptomyces Sp Ach 50mentioning
confidence: 76%
See 1 more Smart Citation
“…Previous studies have demonstrated that Streptomyces sp. AcH 505 can promote the mycorrhizal colonization rate at different stages of bacteriumefunguseplant interactions, including spore germination, thereby acting as a mycorrhizal helper bacteria (Riedlinger et al, 2006;Tarkka and Frey-Klett, 2008;Kurth et al, 2013). In the present study Streptomyces fostered the growth of P. croceum in oaks at stage B, according to the higher amounts of specific FA biomarkers for the respective symbiont (18:1 u9 and 18:2 u6,9) at second harvest.…”
Section: Effect Of Pratylenchus Penetrans and Streptomyces Sp Ach 50mentioning
confidence: 76%
“…The amount of AcH 505 was estimated from soil samples by quantitative real-time PCR (Smith and Osborn, 2009) according to Kurth et al (2013) with primers targeting the intergenic region between the gyrA and gyrB genes of the AcH 505 genome. Briefly, total DNA was extracted from soil samples and DNA quantity and quality were estimated using a spectrophotometer and agarose gel electrophoresis.…”
Section: Quantification Of Pratylenchus Penetrans and Streptomyces Spmentioning
confidence: 99%
“…Given that B. edulis is a comparatively slow growing ECM fungus in saprophytic conditions (Olaizola 2007), P. fluorescens and B. edulis may be competing for nutrients during the presymbiotic period, and consequently, B. edulis may have not been benefited by the bacteria before mycorrhization. Kurth et al (2013) also suggested that the competition between fungus and bacteria for resources may inhibit mycorrhizal development, and Duponnois (1992) reported that high bacterial inoculum doses may also inhibit mycorrhizal development. Thus, the development of methods to quantify the abundance of bacteria and fungus in the presence of one another needs further investigation.…”
Section: Discussionmentioning
confidence: 96%
“…In either case, they are referred to as MHB (Garbaye 1994). The mechanisms by which bacteria interact with fungi involve the stimulation of mycelial growth, the increase of contact points between roots and fungi, and the reduction of environmental stress on the mycelium (Brulé et al 2001;Kurth et al 2013). Nonetheless, the activity of bacteria can also be detrimental to the mycorrhizal symbiosis in some cases (Kataoka et al 2009).…”
Section: Introductionmentioning
confidence: 96%
“…There is also an option of using a co-inoculation approach; literature confirms that mycorrhizal fungi used with PGPR may act synergistically (Gamalero et al 2010). An important amount of soil microorganisms are known as mycorrhization helper bacteria (MHB), which are capable to stimulate hyphal growth and assist mycorrhization (Kurth et al 2013). Some of the main MHBs are members of Agrobacterium, Azospirillum, Azotobacter, Burkholderia, Bradyrhizobium, Enterobacter, Pseudomonas, Klebsiella, Rhizobium, Bacillus, Brevibacillus, Paenibacillus, Rhodococcus, Streptomyces, Arthrobacter genera (Frey-Klett et al 2007).…”
Section: Beneficial Soil Microorganisms -Plant Growth-promoting Rhizomentioning
confidence: 99%